Sex differences in survival of patients with type 2 diabetes in primary care (ZODIAC-50) - Hendriks, Steven H (BMJ Open, 2017)
OBJECTIVE: To investigate sex differences in survival of primary care treated patients with type 2 diabetes (T2D) in the Netherlands. SETTING: Primary care. PARTICIPANTS: A total of 1815 patients who participated in a prospective observational cohort study (Zwolle Outpatient Diabetes Project Integrating Available Care (ZODIAC)) were included of which 56% was female. Inclusion took place in 1998, 1999 and 2001. Vital status was assessed in 2013. MAIN OUTCOME MEASURE: Relative survival of men and women with T2D. The relative survival rate was expressed as the ratio of observed survival of patients divided by the survival of the general population in the Netherlands with comparable age. RESULTS: After 14 years, 888 (49%) patients had died. The relative survival rate was 0.88 (0.81–0.94) for men and 0.82 (0.76–0.87) for women with T2D after 14 years (p value for difference between sexes=0.169). In patients without a history of cardiovascular diseases (CVD), the relative survival was 0.99 (0.94–1.05) in men and 0.92 (0.87–0.97) in women (p value for difference between sexes=0.046). CONCLUSIONS: The survival of men and women with T2D was 12% and 18% lower, respectively, after 14 years of follow-up compared with men and women in the general population. This corresponds to a decrease in median survival of 2.2 and 3.5 years in men and women, respectively. Only for patients with T2D without a history of CVD, a significantly lower relative survival in women compared with men with T2D was found.